THU0638-HPR PHYSICAL ACTIVITY LEVELS OF RADIOGRAPHIC AND NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS PATIENTS. (2nd June 2020) - Yuksel-Karsli, T.; Bayraktar, D.; Ozer Kaya, D.; Gerçik, Ö.; Gucenmez, S.; Oz, H. E.; Solmaz, D.; Akar, S.
Abstract : Background: It is known that cardiovascular disease risk is increased in chronic inflammatory diseases. Additionally, regular exercise is one of the main components of the management of patients with axial spondyloarthritis (axSpA). However, it was reported that axSpA patients do not meet recommended physical activity levels. It is still unknown, whether the disease subgroups of axSpA play a role in participating in physical activity. Objectives: To compare the physical activity levels among radiographic, non-radiographic axSpA patients, and healthy controls. Methods: Thirty-three patients with radiographic axSpA (23 [70%] male), 33 patients with non-radiographic axSpA (23 [70%] male) and 33 age and sex matched healthy controls (23 male [70%]) were included in the study. axSpA patients were assessed regarding to disease activity (Bath Ankylosing Spondylitis Disease Activity Index; BASDAI), functional status (Bath Ankylosing Spondylitis Functional Index; BASFI), spinal mobility (Bath Ankylosing Spondylitis Metrology Index; BASMI). Physical activity level of all subjects was measured by using an accelerometer (Actigraph wGT3X-BT) which was worn on the waist for seven consecutive days. Results: The groups were similar in terms of physical characteristics (age and body mass index) (p>0.05). Disease related characteristics (BASMI, BASFI, BASDAI) were comparable between radiographic and non-radiographic axSpA patients (p>0.05). Radiographic axSpA patients showed lesser physical activity compared to non-radiographic axSpA patients and healthy controls (p<0.05, Table 1 ). There is no difference between non-radiographic axSpA patients and healthy controls regarding the physical activity levels (p>0.05). Conclusion: The results of the present study suggest that radiographic damage in axSpA may alter the physical activity levels. Every effort should be taken to increase physical activity levels in axSpA patients, especially in radiographic cases. Acknowledgments: This project was supported by Izmir Katip Celebi University Scientific Research Projects Coordinatorship. Disclosure of Interests: None declared